2021
DOI: 10.1007/s10792-021-01944-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes, predictability and rotational stability following implantation of Eyecryl toric versus TECNIS toric intraocular lenses—A comparative study

Abstract: Purpose To compare the visual outcomes, predictability and rotational stability following implantation of Eyecryl toric versus TECNIS toric intraocular lenses. Methods This retrospective study included 100 eyes of 78 eligible patients who underwent phacoemulsification followed by implantation of either Eyecryl Toric IOL or TECNIS Toric IOL (n = 50 eyes in each group), using an intraoperative image-guided marker less system. All toric IOL implantations were performed under balanced salt solution. At 2 weeks, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…The TECNIS Toric II IOL (Model ZCU) demonstrated minimal postoperative rotation following implantation, which was reproducible between studies over the full dioptric power range. Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4,9,10,12,[17][18][19] confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5,9,18,[20][21][22][23][24] the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25,26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°).…”
Section: Discussioncontrasting
confidence: 54%
“…The TECNIS Toric II IOL (Model ZCU) demonstrated minimal postoperative rotation following implantation, which was reproducible between studies over the full dioptric power range. Mean absolute lens rotation was less than 1° at both the 1-day and 1-week visits, which was less than previously reported for the TECNIS Toric IOL (1° to 8.38°), 4,9,10,12,[17][18][19] confirming that the squared and frosted haptic design improved rotational stability. These data compared favorably with absolute rotation reported for other toric IOL models, including with the AcrySof Toric IOL (Alcon Laboratories, Inc., Fort Worth, TX, USA) (1.5° to 8.0°), 5,9,18,[20][21][22][23][24] the enVista Toric IOL (Bausch+Lomb, Inc. Rochester, NY, USA) (1.11° to 3.85°), 25,26 and the HOYA XY-1 (HOYA, Tokyo, Japan) (5.43°).…”
Section: Discussioncontrasting
confidence: 54%
“…Rotational stability of toric IOLs has been suggested to be questionable in eyes with preoperative large ALs, due to various factors increasing the likelihood and amplitude of postoperative rotation. [24][25][26][27] When we compared the 3month outcomes of Vivinex Toric IOL in normal vs high AL groups in the present retrospective study, we did not find any significant differences for postoperative outcomes, and rotational stability at 3-month follow-up. Our results resonate with the results of Guo et al, wherein the authors observed an equal astigmatism-correction efficiency and rotational stability in eyes with normal vs high myopia after implantation of the Acrysof IQ toric IOL.…”
Section: Discussionmentioning
confidence: 50%
“…According to the findings of our study, patients with corneal astigmatism who had toric AcrySof and Eyecryl IOLs implanted after cataract surgery saw comparable visual results and astigmatism reduction, which are in line with similar studies. [ 1 4 9 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 ] Nevertheless, this study is the first to directly examine the results of a known international toric IOL, such as AcrySof toric, with those of an Indian-made toric IOL, Eyecryl, in a secondary center in South India. Post-operative UCVA at 1 month was comparable between the two toric IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…An IOL rotation of more than 10 degrees post-operatively was discovered in up to 7% of eyes across several studies involving all commonly used toric IOLs, with a high axial length, a younger age, greater pre-surgical astigmatism, and with the rule astigmatism patients having the highest rotation within the first 10 days post surgery. [ 9 10 11 12 18 20 21 22 24 29 30 43 44 ] IOL rotation less than 10 degrees typically does not require re-surgery. It has been found that hydrophobic acrylic lenses have better rotational stability than other IOL materials.…”
Section: Discussionmentioning
confidence: 99%